STUDI PERILAKU MAHASISWA DALAM POLA PENGAMBILAN KEPUTUSAN PENGGUNAAN JASA BIMBINGAN BELAJAR (Studi pada Jasa Bimbingan Belajar Mahasiswa Buka Buku dengan Pendekatan Studi Kasus) - Al Caesar, M. Rizky; Sukresna, I Made (Diponegoro Journal of Management, 2017)
Buka Buku is the only business that is engaged in education services that are presented to students for tutoring services. Buka Buku itself is currently focused on Undip, exactly to help academics students of the Faculty of Economics and Business Undip. However, Buka Buku experienced a gap between S-I and D-III students in students purchasing power. It affects the difference of class proportion between S-I and D-III students. This study aims to determine the behavior of students that occur today, and the impact of student behavior on the pattern of decision making use of tutoring services Buka Buku. In addition, this study aims to know the right way in serving students, especially the segment of students Diploma III.This research uses Theory of Planned Behavior theory. There are three main variables in the theory in determining the intention of behaving a person, where the intention is to form a person's behavior.  These  variables  are  attitude  toward  the  behavior, perceived  norm,  and  perceived behavioral control. Methods and approaches conducted in this study using qualitative research methods with case study approach. The preparation of this research using Patton model with Miles and Huberman model analysis technique.The result of the research shows how the student behavior, to know the factors causing student decision making. In addition, this study presents the decision making pattern of the use of Buka Buku services based on the relationship between the factors that make up student decisions. Therefore, an effective strategy can be done in serving the student segment at the Faculty of Economics and Business Undip, especially the D-III students.